Phylogenetic analysis of wild bananas (Musa spp.) in West Kalimantan, Indonesia, based on maturase K (matK) genes - HAYATUL FAJRI; ARI SUNANDAR; MAHWAR QURBANIAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fajri H, Sunandar A, Qurbaniah M. 2024. Phylogenetic analysis of wild bananas (Musa spp.) in West Kalimantan, Indonesia, based on maturase K (matK) genes. Biodiversitas 25: 2612-2618. West Kalimantan is home to wild bananas (Musa spp.). Genetic assessment of wild banana relatives is important for future breeding purposes. This study aims to analyze the phylogenetic relationship of wild banana species in West Kalimantan based on maturase K (matK) gene sequence data to understand better the relationship among wild banana species in West Kalimantan. A total of 30 samples, including 23 matK sequences from GenBank, were used. Species of Heliconia schiedeana were incorporated as an outgroup. The phylogenetic analysis was conducted using the Maximum Likelihood (ML) algorithm in MEGA 11 application. The size of PCR-amplified matK is estimated at 540-561 bp. It showed high variability with conservation level A+T, with an average value was 66.26%. Some unique nucleotides were found in Musa acuminata subsp. microcarpa, Musa campestris, and Musa borneensis. The matK sequences of Musa spp. have a polymorphic site on 23 nucleotide numbers. The phylogenetic analysis with ML algorithm of 30 Musa spp. from West Kalimantan and GenBank data was successfully divided into two main cladesbootstrap value. Our study showed that matK genes are able to describe the differences in M. acuminata, M. campestris, and M. borneensis in West Kalimantan. This study will benefit taxonomic, genetic conservation strategy, and banana breeding efforts. It will provide valuable insights and tools for these fields, thereby contributing to the conservation and breeding of bananas.